2022
DOI: 10.3390/s22186740
|View full text |Cite
|
Sign up to set email alerts
|

A Customer Behavior Recognition Method for Flexibly Adapting to Target Changes in Retail Stores

Abstract: To provide analytic materials for business management for smart retail solutions, it is essential to recognize various customer behaviors (CB) from video footage acquired by in-store cameras. Along with frequent changes in needs and environments, such as promotion plans, product categories, in-store layouts, etc., the targets of customer behavior recognition (CBR) also change frequently. Therefore, one of the requirements of the CBR method is the flexibility to adapt to changes in recognition targets. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Compared to other machine learning algorithms, HMM will not appear overfitted due to the increase in the number of hidden states, nor will the prediction accuracy decrease with the increase in the number of input features [64]. This has been verified in other scholars' studies, where HMM has shown better prediction performance [65][66][67]. However, the prediction results have specific errors since the training samples cannot cover all the observed states.…”
Section: Discussionmentioning
confidence: 75%
“…Compared to other machine learning algorithms, HMM will not appear overfitted due to the increase in the number of hidden states, nor will the prediction accuracy decrease with the increase in the number of input features [64]. This has been verified in other scholars' studies, where HMM has shown better prediction performance [65][66][67]. However, the prediction results have specific errors since the training samples cannot cover all the observed states.…”
Section: Discussionmentioning
confidence: 75%
“…The information obtained can then be used to devise marketing strategies. More recently, in [35], Wen et al proposed making use of customer behaviour primitives in conjunction with object tracking to achieve accurate customer behaviour recognition. In [36], Radhakrishnan et al also looked at detecting such activities, but instead by using sensor data from wearable devices in combination with smartphones.…”
Section: State Of the Art In Iotmentioning
confidence: 99%
“… Customer Experience: ODT can extract the customer's actions during store visits. It can assist in understanding the possibilities of assistance that any visiting customer may require [24].…”
Section: Retail Usagementioning
confidence: 99%